Rosuvastatin mitigates blood–brain barrier disruption in sepsis-associated encephalopathy by restoring occludin levels - Qin Shen; Qian Yu; Taojiang Chen; Lijuan Zhang (European Journal of Medical Research, 2025)
Abstract Background Blood–brain barrier (BBB) disruption is a key pathological feature of sepsis-associated encephalopathy (SAE). Rosuvastatin, a third-generation statin, exhibits diverse pharmacological functions beyond its lipid-lowering capacity. However, its potential neuroprotective role in SAE remains unclear. Materials and methods SAE models were established using the cecal ligation and puncture (CLP) method. BBB integrity was evaluated using NaF, and endothelial permeability was assessed by fluorescein isothiocyanate (FITC)-dextran assays. Results Rosuvastatin significantly attenuated neuroinflammation in the brains of septic mice by reducing the expression of the pro-inflammatory cytokines interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and tumor necrosis factor α (TNF-α). It also ameliorated vascular injury in the brain cortex of septic mice by decreasing the levels of vascular cell adhesion molecule-1 (VCAM-1) and E-selectin. Furthermore, Rosuvastatin preserved BBB integrity in septic mice by enhancing the expression of the tight junction protein occludin. In vitro studies demonstrated that Rosuvastatin alleviated endothelial permeability and increased transendothelial electrical resistance (TEER) in lipopolysaccharide (LPS)-stimulated human brain microvascular endothelial cells (HBMECs). Additionally, Rosuvastatin prevented the LPS-induced reduction of occludin and Krüppel-like factor 2 (KLF2) in HBMECs. Importantly, silencing KLF2 abrogated Rosuvastatin's protective effects on endothelial permeability and occludin expression. Conclusions These findings indicate that Rosuvastatin may be a promising therapeutic candidate for mitigating BBB dysfunction associated with SAE.